5,5′-(Disulfanediyl)bis(1-methyl-1H-tetrazole) - Cui, Ai-Yun (International Union of Crystallography, 2011)
In the title molecule, C(4)H(6)N(8)S(2), two tetrazole rings linked by a disulfide bridge form a dihedral angle of 71.32 (7)° [C—S—S—C torsion angle = −80.51 (10)°]. In the crystal, strong intermolecular π–π interactions between the tetrazole rings [centroid–centroid distance = 3.285 (3) Å] link pairs of molecules into centrosymmetric dimers. Weak intermolecular C—H⋯N hydrogen bonds further link these dimers, related by translation in the [100] direction, into columns.